Fungsi Kepala Sekolah dalam Menerapkan Manajemen Pendidikan di SMK Darunnajah Bogor - Annas Tasya Astuti; Khairrina Khairrina; Irman Sumantri; Arizqi Ihsan Pratama (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the ability of principals at SMK Darunnajah Bogor in implementing education management and to determine the supporting and inhibiting factors. The research method used in this study is a qualitative descriptive approach. Data collection techniques using observation, interviews, and documentation as well as testing the validity of the data by triangulation. The results of the study show that the principal in carrying out his functions can be concluded that he has done well and optimally in terms of his performance and ability to implement education management at Darunnajah Vocational High School Bogor from time to time which is getting better. In its implementation, the principal is also assisted by educators and educational staff in carrying out their duties so that the goals are achieved as expected. Supporting factors for the implementation of education management, namely management executives believe that support from institutional leaders, school principals, as well as adequate facilities and infrastructure are the supporting factors and the main factors that make education management run well, namely the existence of verbal and moral motivation to employee. Meanwhile, the inhibiting factors in implementing education management are that management executives are hampered in terms of infrastructure that are less prime in their use, then in terms of human resources teachers still need to learn more to master programs to make it easier to carry out existing tasks.